The use of a visual motor test to identify lingering deficits in concussed collegiate athletes - Hunzinger, Katherine J. (J Clin Transl Res, 2020)
BACKGROUND: Emerging evidence suggests neurophysiological deficits, such as visual motor coordination (VMC), may persist beyond clinical concussion recovery. Instrumented measurement of upper-limb VMC is critical for neurological evaluation post-concussion and may identify persistent deficits further elucidating persistent neurophysiological impairments not detected by the current clinical assessment battery. AIM: The aim of the study was to determine if a VMC test identifies persistent deficits in concussed collegiate student-athletes who have returned to baseline on clinical concussion assessments. METHODS: Thirteen recently concussed intercollegiate student-athletes (male: 7, 18.9±0.7 years, 175.5±12.4 cm, 75.5±23.2 kg), and 13 matched control student-athletes (male: 7, 19.3±1.1 years, 173.5±11.9 cm, 75.8±19.9 kg) completed two testing sessions (T1: <48 h after clinical recovery; T2: 30 days post-concussion) on a visual motor exam. The outcome measures were A* Average score (average number of lights hit on A* exam), simple visual reaction time (SVRT)-RT, and movement time (SVRT-MT) on the Dynavision D2. The dependent variables were compared with a 2 (group) × 2 (time) repeated measures ANOVAs. RESULTS: There was no group interaction in A* average score (F(1,24)=0.036, P=0.849), SVRT-RT (F(1,22)=0.319, P=0.575), and SVRT-MT (F(1,22)=1.179, P=0.188). There was a main effect for time on A* average score (T1: 76.3±10.4 hits; T2: 82.7±11.2 hits; F(1,24)=38.1, P≤0.001) and SVRT-RT (T1: 0.31±0.04; T2: 0.29±0.04 s; F(1,22)=4.9, P=0.039). There was no main effect for SVRT-MT. There were no group differences at either time point. CONCLUSIONS: Among recently concussed collegiate student-athletes, no persistent deficits were identified in VMC beyond clinical recovery when assessed by Dynavision D2. This VMC exam may not provide a useful means of tracking recovery following concussion likely due to a substantial practice effect. RELEVANCE FOR PATIENTS: While post-concussion neurophysiological deficits persist beyond clinical recovery, the laboratory based VMC assessment herein did not identify deficits at critical post-concussion time points. Therefore, other clinically translatable VMC assessments should be further investigated.